PERANAN PERKEBUNAN KARET TERHADAP PEMBANGUNAN EKONOMI WILAYAH DI KABUPATEN BATANGHARI - Sianturi, Nancy Irawaty; Mara, Armen; Fathoni, Zakky (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
This research was aimed to (1) know the role of rubber plantation on regional economic development in Batanghari Regency, (2) know and analyze the impact of rubber plantation on regional income and labor in Batanghari Regency, (3) know the relation of rubber plantation production with GDRP manufacturing industry, GDRP transportation and communication, and GDRP trade, hotels and restaurant. This research used Location Quotient (LQ) analysis, Shift-Share analysis, multiplier analysis, and correlation analysis. Based on the analysis, the result showed that rubber plantation contribute positively to GDRP and labor and its position as the base sector that drives other sectors. Calculation of shift-share analysis obtained by the growth of rubber plantation in Batanghari Regency has a fast growing income growth but at the level of Jambi Province grows slowly or is degenerate. Based on multiplier analysis on regional income was 23,24 and labor was 2,69 which means that every Rp 1,- increased income and 1 person labor on a rubber plantation will contribute to regional income and labor Rp 23,24 billion and 2,69 people or rounded to 3 people. Correlation analysis produce a close and positive relation between rubber plantation production with GDRP manufacturing